Carbon isotopes and water use efficiency in C4 plants. (June 2016) - Ellsworth, Patrick Z; Cousins, Asaph B
Highlights: WUE is an important trait in plant breeding but it is difficult to phenotype. Using leaf carbon isotopes to screen for water use efficiency in C4 crops discussed. Effect of leakiness and post-photosynthetic fractionations on leaf δ 13 C need more research. Abstract : Drought is a major agricultural problem worldwide. Therefore, selection for increased water use efficiency (WUE) in food and biofuel crop species will be an important trait in plant breeding programs. The leaf carbon isotopic composition (δ 13 Cleaf ) has been suggested to serve as a rapid and effective high throughput phenotyping method for WUE in both C3 and C4 species. This is because WUE, leaf carbon discrimination (Δ 13 Cleaf ), and δ 13 Cleaf are correlated through their relationships with intercellular to ambient CO2 partial pressures ( C i / C a ). However, in C4 plants, changing environmental conditions may influence photosynthetic efficiency (bundle-sheath leakiness) and post-photosynthetic fractionation that will potentially alter the relationship between δ 13 Cleaf and C i / C a . Here we discuss how these factors influence the relationship between δ 13 Cleaf and WUE, and the potential of using δ 13 Cleaf as a meaningful proxy for WUE.